Institutions and service employment: a panel study for OECD countries - Julián Messina (European Central Bank (ECB), 2004)
We live in a service economy, but the extent of development of service employment differs across developed countries. This paper assesses the role of structural factors and institutions in explaining the common patterns and main di?erences in the recent expansion of service employment in OECD countries. It finds that GDP per capita, the size of the government sector and the extent of urbanization are positively associated with the service employment share. However, the evidence suggests that laws and institutions such as product market regulations, unions and more coordinated wage-setting systems are hampering the expansion of service employment.
Keywords: J21; L80; L51; 330; Employment; Product and Labor Market Regulations; Service Industries; Structural change